Columnar-to-Equiaxed Transition in Metal-Matrix Composites Reinforced with Silicon Carbide Particles - Ares, Alicia Esther (2013)
The present work is focused on the study of the effect of directional heat extraction on the silicon-carbide (SiC) distribution in zinc-aluminum matrix composites (MMCs) and on the columnar-to-equiaxed (CET) position in directionally solidified samples. To this end, a ZA-27 alloy matrix was reinforced with ceramic particles of SiC and vertically directionally solidified. The cooling rates, temperature gradients, and interphase velocities were then measured, and their influence on the solidification microstructure of the MMCs was analyzed. The recalescence detected and measured during the equiaxed transition was of the order of 3.5∘ C to 1.1∘ C. The values of the temperature gradients reached a minimum during the CET and were even negative in most cases (between −3.89 K and 0.06 K). The interphase velocities varied between 0.07 mm/s and 0.44 mm/s at the transition. Also, the presence of ceramic particles in ZA-27 alloys affected the thermodynamic local conditions and the kinetics of nucleation, producing a finer microstructure.